2021
DOI: 10.1108/jedt-05-2020-0171
|View full text |Cite
|
Sign up to set email alerts
|

Key driving factors of cost overrun in highway infrastructure projects in Nigeria: a context-based perspective

Abstract: Purpose Extensive research towards identifying the attributable cost overrun factors globally has been conducted predominantly from a survey-oriented perspective, which disregard the contextual basis on which these triggers manifest. This study aims to explore the driving factors of cost overrun in highway projects, specific to the Nigerian context. Design/methodology/approach The research used a context-based approach to seek project stakeholders’ perspectives on the key drivers of cost overrun in highway p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 41 publications
1
13
0
3
Order By: Relevance
“…Gardezi et al (2014) observe that project funding is one of the primary sources that enable parties to a contract to complete the project within time. Kazemi et al (2021) and Mahmud et al (2021) identified owner financial problems leading to payment delays as contributing factors to project delays. The delayed payments tend to result in disputes between the client and contractor, which may later lead to slow down progress, contract termination, arbitration, litigations, claims for time extension and cost overrun (Amoatey et al , 2015).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gardezi et al (2014) observe that project funding is one of the primary sources that enable parties to a contract to complete the project within time. Kazemi et al (2021) and Mahmud et al (2021) identified owner financial problems leading to payment delays as contributing factors to project delays. The delayed payments tend to result in disputes between the client and contractor, which may later lead to slow down progress, contract termination, arbitration, litigations, claims for time extension and cost overrun (Amoatey et al , 2015).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Factors such as financial problems, unrealistic contract durations imposed by clients, poorly defined project scope, client-initiated variations, under-estimation of the project cost by consultants, poor consultants project inspection and supervision, contractors underestimation of project complexity, poor site management, use of inappropriate construction methods by contractors and delays in the issuance of permits by government agencies are some of the significant causes of project delays in Ghana (Famiyeh et al , 2017). Mahmud et al (2021) also identified key triggers of project delays as delay in work progress, political instability, adverse weather, social issues, delay in progress payment to contractors and project scope modifications.…”
Section: Introductionmentioning
confidence: 99%
“…[20], [55], [58], [104], [105], [106], [88], [99], [66], [107] , [12], [68], [100], [91], [70], [108] [79], [42], [81], [109], [110], [47], [45], [49], [95], [111], [54], [112], [59], [25], [87], [105], [106], [10], [65], [113], [12], [89], [100], [69], [90], [108], [75], [76]…”
Section: Rank the Top Five Critical Cost Overrun Causesunclassified
“…[26], [29], [34], [77], [37], [40], [15], [79], [42], [81], [109], [110], [47], [45], [49], [95], [111], [54], [112], [87], [59], [25], [105], [106], [10], [65], [113], [12], [89], [100], [69], [90], [108], [75], [76] 35 Poor decision-making process and delay in taking decisions [114], [101], [81], [47], [49], [50], [119], [84], [87], [105], [100], [92], [75] 13 Clients' practice for tendering and awarding…”
Section: Rank Cost Overrun Causes Based On the Related Stakeholder Ca...mentioning
confidence: 99%
See 1 more Smart Citation